Pengaruh Ukuran Bank, Struktur Modal, Suku Bunga Dan Loan To Deposit Ratio Terhadap Profitabilitas Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Evonella Nainggolan; Jessy Safitri Sitorus (COSTING : Journal of Economic, Business and Accounting, 2021)
Banking in carrying out its operational activities is always required to achieve high profitability. This study aims to examine the effect of Bank Size, Capital Structure, Interest Rates and Loan to Deposit Ratio on the Profitability of Banking Companies Listed on the Indonesia Stock Exchange 2016-2019 Period. The approach that processes the research data is a quantitative approach. The population in this study were 43 companies with 25 samples of banking companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The data analysis method used is multiple linear regression test. The results of this study are that Bank Size has an effect on Profitability, Capital Structure has an effect on Profitability, Interest Rates have no effect on Profitability, and Loan to Deposit Ratio has no effect on Profitability in Banking Companies Listed on the Indonesia Stock Exchange Period 2016-2019. Simultaneously, Bank Size, Capital Structure, Interest Rate and Loan to Deposit Ratio affect the Profitability of Banking Companies Listed on the Indonesia Stock Exchange 2016-2019 Period. Keywords: Bank Size, Capital Structure, Interest Rates, Loan to Deposit Ratio and Profitability. Keywords : Bank Size, Capital Structure, Interest Rates, Loan to Deposit Ratio and Profitability.